2023
DOI: 10.1039/d2sm01207c
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced destabilisation of oil-in-water emulsions using light-active bolaform surfactants

Abstract: External stimuli induced destabilisation of oil-in-water emulsions is of both fundamental and tech- nological importance. In this work we synthesize light-active bolaform-type surfactants (LABS) and show the preparation of decane-in-water...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A persistent random walk model along boundaries was found to capture the observed time-distributions to escape the dynamical traps posed by the pore-throats. 351 Active polymer models where simple steric interactions are emphasized have a significant role to play in determining general principles of transport in this limit. [352][353][354] The importance of body shape, stroke, and topology is receiving attention in determining the dynamics of bacteria as also discussed in the following Section 4.2.…”
Section: Intruder Dynamics In Granular Sediments -A Kudrollimentioning
confidence: 99%
“…A persistent random walk model along boundaries was found to capture the observed time-distributions to escape the dynamical traps posed by the pore-throats. 351 Active polymer models where simple steric interactions are emphasized have a significant role to play in determining general principles of transport in this limit. [352][353][354] The importance of body shape, stroke, and topology is receiving attention in determining the dynamics of bacteria as also discussed in the following Section 4.2.…”
Section: Intruder Dynamics In Granular Sediments -A Kudrollimentioning
confidence: 99%
“…Likewise, a separate simulation investigation 42 of an active nanorod confined within a circular region with single and multiple escape openings highlighted the critical significance of the nanorod's activity and its persistence length in optimizing its escape time. Simultaneously, an experimental endeavor revealed that confined undulating worms 43 placed in interconnected circular chambers via a narrow channel escape a chamber by consistently traversing along the boundary of the chamber. So far in the above literature and to the best of our knowledge the effect of chiral activity on narrow escape kinetics and segregation of bi/multimotility mixtures has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated demulsification of Pickering emulsion by a interfacial transport of mutually soluble cosolvent. 11 Recent developments have shown that Pickering emulsions can be demulsified using external stimuli such as light intensity, 12 pH, ionic strength, CO 2 , and magnetic field, either individually or in combinations. 13 In this study, we show the proof of concept of a demulsification mechanism that involves partial chemical dissolution of the stabilizing particle.…”
Section: ■ Introductionmentioning
confidence: 99%